Hubungan Demografi Pasien terhadap Kepatuhan Pengambilan Ulang Obat Antiretroviral Pasien HIV/AIDS di Poli Rawat Jalan RS X - Leonov Rianto; Aripin; Aries Meryta; Siti Romlah (Jurnal Ilmu Farmasi Terapan dan Kesehatan, 2025)
This study aims to evaluate adherence to antiretroviral (ARV) drug refills among HIV/AIDS patients at the outpatient clinic of Hospital X in West Jakarta. Adherence is defined as the patient's conscious commitment to follow their treatment, not merely obeying the doctor's orders. Non-adherence is a common cause of ARV therapy failure. One form of non-adherence is not obtaining prescription refills (refills not obtained). This study used a quantitative descriptive design with the Medication Possession Ratio (MPR) method to measure adherence. Patients were considered adherent if the MPR percentage was ≥80% and non-adherent if <80%. The results from the period of March-May 2022 showed that out of 123 patients, 117 (95.1%) were adherent in obtaining prescription refills, while 6 (4.9%) were non-adherent. Statistical analysis revealed no significant relationship between gender and adherence levels to drug refills. These findings indicate that the majority of HIV/AIDS patients at Hospital X in West Jakarta have high adherence to ARV treatment. However, regular monitoring and evaluation of adherence remain necessary to ensure treatment success and prevent therapy failure. This study emphasizes the importance of patient awareness in consistently following ARV therapy.